Understanding the Needs of Primary School Teachers in Supporting Their Students' Emotion Regulation. (16th May 2022) - Petrovic, Julia; Mettler, Jessica; Argento, Amanda; Carsley, Dana; Bloom, Elana; Sullivan, Shaun; Heath, Nancy L.
ABSTRACT: Background: Accumulating evidence has underscored the importance of fostering children's emotion regulation (ER) within primary school settings and the role of teachers in such efforts. This study sought to assess the needs of teachers in supporting students' ER, through a better understanding of teachers' perceptions and use of healthy versus unhealthy ER strategies in the classroom. Methods: Primary school teachers ( n  = 212; 91% female) completed an online, researcher‐developed needs assessment survey assessing their perceptions regarding the importance of ER instruction and challenges surrounding children's ER, as well as the perceived effectiveness and reported use of healthy and unhealthy ER strategies in the classroom. Results: Cochran's Q and chi‐square analyses revealed misperceptions regarding the effectiveness of healthy and unhealthy strategies, as well as discrepancies between teachers' perceptions regarding the effectiveness of specific healthy strategies (eg, meditation) and their reported use of them. Conclusions: While teachers recognize the growing importance of fostering ER in the classroom, the present findings suggest that there is a need for more professional development regarding the effectiveness and implementation of ER strategies in the primary school context. Efforts should be made to provide teachers with concrete recommendations for the implementation of ER strategies in the classroom.